New-onset type 1 diabetes in Finnish children during the COVID-19 pandemic - Salmi, Heli; Heinonen, Santtu; Hästbacka, Johanna; Lääperi, Mitja; Rautiainen, Paula; Miettinen, Päivi J; Vapalahti, Olli; Hepojoki, Jussi; Knip, Mikael (Archives of disease in childhood, 2022)
BackgroundViral infections may trigger type 1 diabetes (T1D), and recent reports suggest an increased incidence of paediatric T1D and/or diabetic ketoacidosis (DKA) during the COVID-19 pandemic.ObjectiveTo study whether the number of children admitted to the paediatric intensive care unit (PICU) for DKA due to new-onset T1D increased during the COVID-19 pandemic, and whether SARS-CoV-2 infection plays a role.MethodsThis retrospective cohort study comprises two datasets: (1) children admitted to PICU due to new-onset T1D and (2) children diagnosed with new-onset T1D and registered to the Finnish Pediatric Diabetes Registry in the Helsinki University Hospital from 1 April to 31 October in 2016–2020. We compared the incidence, number and characteristics of children with newly diagnosed T1D between the prepandemic and pandemic periods.ResultsThe number of children admitted to PICU due to new-onset T1D increased from an average of 6.25 admissions in 2016–2019 to 20 admissions in 2020 (incidence rate ratio [IRR] 3.24 [95% CI 1.80 to 5.83]; p=0.0001). On average, 57.75 children were registered to the FPDR in 2016–2019, as compared with 84 in 2020 (IRR 1.45; 95% CI 1.13 to 1.86; p=0.004). 33 of the children diagnosed in 2020 were analysed for SARS-CoV-2 antibodies, and all were negative.ConclusionsMore children with T1D had severe DKA at diagnosis during the pandemic. This was not a consequence of SARS-CoV-2 infection. Instead, it probably stems from delays in diagnosis following changes in parental behaviour and healthcare accessibility.